The Effects of Brain-based Learning Strategies on Low Ability Malaysian English as a Second Language Learners’ Writing Performance - Albert, Wilson; Joseph, Ramanair; Soubakeavathi, Rethinasamy (UPM, 2024)
The main goal of Brain-based Learning (BBL) is to create effective learning conditions that allow the brain to naturally learn. A plethora of studies on BBL learner performance and perceptions have been conducted in a variety of contexts. However, BBL studies on low-ability ESL learners are still in their infancy. Therefore, this study investigated low-ability ESL Malaysian learners’ BBL performance and perceptions in the classroom. A purposive sampling technique is used to collect quantitative data from 150 learners. A quasi-experimental design compares the learners’ pretest and post-test scores. The descriptive analysis indicated a favorable outcome when the post-test mean score was higher than the pretest scores in the literature critical response writing test. A pair sample t-test was also conducted, and results showed that there is a statistically significant improvement in the scores from the pretest (M = 2.45, SD = 1.50) to the post-test (M = 5.35, SD = 2.40), t(149) = -15.48, p<.05. A qualitative design is also used to investigate three learner-focus groups’ (five in each group) responses after BBL intervention. Findings revealed that there are generally positive responses related to the BBL theoretical framework of this study. However, there are some negative responses pertaining to two components of the framework. This study indicates that BBL can enhance low-ability ESL learners’ writing performance and active learning engagement.